Prediction of Plastic Shrinkage Cracking of Self-Compacting Concrete - Parviz Ghoddousi; Armin Monir Abbasi; Esmail Shahrokhinasab; Mohammad Abedin (Advances in Civil Engineering)
Concrete exposed to hot climatic conditions is prone to plastic shrinkage after casting within the first few hours due to the water evaporation and restraining conditions of concrete. This cracking is more commonly observed in concrete elements with a large surface area exposed to drying. In this research, plastic shrinkage of 13 self-compacting concrete samples with different cement paste volumes and various coarse to total aggregate ratios was studied. Test specimens of fresh concrete were subjected to a wind tunnel, which simulated hot dry environmental condition immediately after casting. It can be observed from the test results that the relationship between free plastic shrinkage and the difference between bleeding and evaporation is direct and linear. Finally, a model for plastic shrinkage estimation was suggested by considering the effect of free plastic shrinkage strain, restraining factor, and tensile strain capacity of self-compacting concrete.